(untitled) (CIPEEX, 2022)
SOME AUTHORS ARGUE THAT MUSIC AND THE COMBINATION OF SOUNDS AND SILENCES IN AN ORGANIZED WAY, HOWEVER, DEFINING MUSIC IS NOT SOMETHING SO SIMPLE AND OBVIOUS IN THIS WAY. MORE COMPREHENSIVE AND DIDACTIC, MUSIC IS COMPOSED OF MELODY, HARMONY AND RHYTHM, BEING THAT MELODY IS THE MAIN VOICE OF THE SOUND, IS WHAT CAN BE SUNG, HARMONY, IS AN OVERLAP OF NOTES THAT SERVE AS THE BASIS FOR THE MELODY, IS THE TODAY’S SOCIETY HAS USED MUSIC IN VARIOUS WAYS WITH VARIOUS FUNCTIONS, MUSIC FOR SOCIALIZING, MUSIC FOR ACTIVITIES MUSIC AS A THERAPY AND AMONG OTHERS, WHEREVER YOU LOOK THERE WILL BE MUSIC IN CARS, ON THE STREETS AND IN VARIOUS OTHER PLACES. MUSIC COMES AS A WAY TO GET PEOPLE TO INTEGRATE AND THE MUSIC KNOWN TO SEVERAL PEOPLE IN AN ENVIRONMENT, ONE NOTICES WHISPERS AND SUDDENLY A FULL CHOIR OF SEVERAL VOICES THAT SING THE LYRICS TOGETHER OR EVEN DANCES. THE DRUMS THAT ARE COMPOSED OF PERCUSSION INSTRUMENTS, SUCH AS DEAF, ROCARES (TAMBOURINES), BOXES, TAMBOURINES AND AGOG, WHICH, ACCOMPANIED BY EACH INSTRUMENT, HAVE A PERCUSSIONIST AND A RHYTHMIST THAT SETS THE RHYTHM OF THE INSTRUMENTS, IN THE CASE OF THE DRUMS OF THE DENTISTRY COURSE OF THE UNIVERSITY CENTER OF ANÁPOLIS UNI-EVANGÉLICA, KNOWN AS BROCADORA, HAS BEEN BRINGING TOGETHER DENTISTS FROM VARIOUS PERIODS OF THE COURSE, BRINGING INTEGRATION, INCLUSION AND SOCIALIZATION AMONG THE ACADEMICS. THE COMBINATION OF THE RHYTHM OF THE MUSIC AND ITS PARTICIPANTS, THE TERMS CITED ABOVE, INTEGRATION, INCLUSION AND SOCIALIZATION CONTRIBUTE TO THE IMMERSION OF ACADEMICS IN THE MUSICAL WORLD IN ORDER TO RELIEVE THE STRESSES OF EVERYDAY LIFE, THE CITY AND THE CITY. PRESERVING THE EMOTIONAL AND PSYCHOLOGICAL WELL-BEING, OFTEN ACTING AS AN ESCAPE VALVE.THEREFORE, WE CONCLUDE THAT THE MUSIC IS OF FUNDAMENTAL IMPORTANCE IN SEVERAL ASPECTS, AND THAT IT HELPS A LOT IN THIS RESPECT INTEGRATION OF SOCIETY WITH THIS TYPE OF MUSICAL CULTURE, AND THAT THE BATTERY OF DENTISTRY HAS FOR THE SCHOLARS NEW TIES BETWEEN THEM.&NBSP; KEYWORDS: MUSIC. INCLUSION. SOCIALIZATION. INTEGRATION.